What's Trending Now? An Analysis of Trends in Internet Searches for Labor Epidurals. Issue 1 (March 2018) - Sutton, C.D.; Carvalho, B.
Abstract : ( IJOA . 2017;30:52–57) People now turn to the internet frequently to obtain information about everything. In one survey of parturients, it was found that in 2011 to 2012, 97% of surveyed women used the internet to find information about childbirth. In an effort to see what pregnant women might be concerned about regarding the topic of labor pain management, the current study was undertaken to see how often the term [epidural] showed up in internet searches as well as other terms relating to pain management and birth. In addition, the study analyzed increases in the number of searches over time. The investigators felt the information obtained from the study could help doctors in their communication with patients.